Combination of DCE-MRI and DWI in Predicting the Treatment Effect of Concurrent Chemoradiotherapy in Esophageal Carcinoma. (16th June 2020) - Liu, Changmin; Sun, Roger; Wang, Jing; Ning, Fangling; Wang, Zhenbo; Luo, Judong; Chen, Shaoshui; Yuan, Shuanghu
Abstract : Background. Concurrent chemoradiotherapy (CCRT) is the main treatment for esophageal cancer, but the response to treatment varies from individual to individual. MR imaging methods, such as diffusion-weighted (DW) MRI and the use of dynamic contrast-enhanced (DCE) MRI, have the potential to provide additional biomarkers that could evaluate the effect of CCRT in patients with esophageal carcinoma. Materials and Methods. Fifty-six patients with esophageal carcinoma, verified by histopathology, underwent MRI examination before and at midtreatment (4 th week, radiotherapy 30–40 Gy) using the Siemens 3.0 T MR System. Parameter maps of apparent diffusion coefficient (ADC), and DCE maps of volume transfer constant (K rans ), rate contrast (k ep ), and extracellular fluid space (v e ), were computed using a Siemens Company Multimodality Workplace (MMWP) model. Comparison of histogram parameters and their diagnostic performance was determined using the Mann–Whitney U test and receiver operating characteristic (ROC) analysis. Results. 56 patient MRI scans were available for analysis at baseline and at the third week, respectively. Pretreatment K rans, pretreatment k ep, pretreatment ADC (P < 0.05 ), and during-treatment K rans (P < 0.05 ) and Δ K rans and Δ ADC (P < 0.05 ) were significantly different after CCRT. Based on the binary logistic model, the ROC analysis demonstrated that the combined predictors demonstrated a high diagnostic performance with an AUC of 0.939. The sensitivity and specificity were 98.6% and 73.8%, respectively. Conclusion. The combination of DCE and DWI can be used as an early biomarker in the prediction of the effect of CCRT three weeks after treatment in esophageal carcinoma.